Sustainability Indicators of Kalang Buffalo Production Systems in Swamp Ecosystems in South Kalimantan - Widya Nur Amalia; Tri Satya Mastuti Widi; Panjono Panjono; Dyah Maharani; Sigit Bintara (Buletin Peternakan, 2023)
This study aims to identify problems, identify and analyze stakeholders and determine indicators (qualitative and quantitative) for the sustainability of kalang buffalo production systems in swamp ecosystems in South Kalimantan. The kalang buffalo is a type of mud buffalo that is reared using the kalang system. In the local language, kalang is an enclosure built in the middle of swamp waters. This study is expected to be a source of information for academics, farmers, communities and policymakers in South Kalimantan Province regarding the strategic function of Kalang buffalo for the people of South Kalimantan. Data collection was done by describing the problem and determining relevant stakeholders. The literature study was conducted with expert discussion. FGDs were also conducted to explore important issues, followed by SWOT (Strengths, Weaknesses, Opportunities, and Threats) analysis and to determine relevant issues. Situation analysis and secondary data showed that the Kalang buffalo population is declining. Stakeholder identification identified the central and local governments as primary stakeholders; secondary stakeholders were scientists/academics, butchers, sellers, and consumers. The primary stakeholders selected were buffalo farmers, central and local governments, while secondary stakeholders consisted of scientists/academics, butchers, farmer sellers, and consumers. The selected indicators on the EES issue are economic indicators such as gross margin (GM), body weight, weaning weight, and reproduction (calf crop (%)); environmental indicators such as total grazing land use and waste disposal; and social indicators such total of buffalo, feeding procedures, mating system, cages, record keeping, time allocation for maintenance, social status and land use conflicts.